Aspects of the life cycle of the avian parasite Philornis torquans (Diptera: Muscidae) under laboratory rearing conditions - Saravia Pietropaolo, María José (2018)
The life cycle of the avian parasitic flies Philornis Meinert (Diptera: Muscidae) is poorly known, limiting the understanding of the ecology of these flies, including interactions with their hosts. We provide data on length and survival of pupal and adult stages and the duration of the pre-oviposition period of Philornis torquans Nielsen. Specimens were collected at larval and pupal stages from infested broods. The pupal stage lasted on average 10.5 days and adults lived up to 100 days in the laboratory. At least 90.2% of larvae pupated and 85.7% of the latter emerged as adults. For individuals collected as larvae, pupal mortality was 3.5 times higher than for those collected as pupae. Females laid from 1-8 clutches in their lifetime and deposited, on average, 41 eggs per female (range: 1-148). Females collected as pupae were larger and had shorter pre-oviposition periods and lifespans than females collected as larvae, but there were no differences in the total eggs laid by these females. This is the first information on reproductive parameters of a subcutaneous species of Philornis, and forms the basis for studies on conditions required for reproduction of this species in captivity.